Determinan Probabilitas Obesitas pada Anak di Indonesia: Pendekatan Ekonomi Kesehatan - Hariyani, Fitri; Riani, Novya Zulva (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
The phenomenon of obesity is a serious problem in various countries, especially in Indonesia. Based on (Riskesdas, 2018) the proportion of central obesity at the age of ≥15 years by province in Indonesia, shows that the Indonesian average is 31 percent. One of the factors causing overweight and obesity is socioeconomic factors. This study aims to determine the determinants of the probability of obesity in children. The data used is cross section derived from Basic Health Research (Riskesdas) in 2018 on samples aged 5 to 15 years, with binary logistic regression method. The results of this study indicate that 4.76 percent of children aged 5-15 years are obese, statistically there is an influence between socioeconomic status on the probability of childhood obesity in Indonesia.